THE EMERGENCE AND RESOLUTION OF CONFLICTS IN A SPORTS TEAM - Шарипова, Гульнара; Мустафина, К.К; Макарова, Елена (Modern engineering and innovative technologies, 2022)
In modern society, conflicts have a significant impact on human life and the development of social groups. Their wide distribution often leads to the fact that conflict relationships become decisive in the team. Such relationships lead to mental tension,